MODEL REVISI KEYAKINAN DAN KEPUTUSAN AUDIT: SUATU PENGUJIAN EKSPERIMENTAL - Ayuananda, Tri Ika; Utami, Intiyas (Jurnal Akuntansi dan Keuangan Indonesia, 2015)
The purpose of the research is to assess the recency effect about sequence, manner of presentation and form of information on audit decisions when the information is presented sequentially or simultaneously. Recency effect is a biased decision of the auditor when information is given in sequence and auditors tend to weigh the last information greater than the earlier information. The research used a 2x2x2 experimental design with 80 participants between the subject of undergraduate students majoring in accounting. The results of the research showed that: (i) belief revision occurs when information is presented in the sequential method; and (ii) in the audit decision-making, reviews effects occur in the form of a chart.